Global Economic and Political Interdependencies in the 21st Century: Challenges and Innovations - El Kiasse, Rafik (European Journal of Applied Sciences, 2025)
This article examines the complexities of economic and political interdependencies in the modern globalized world. It explores the impact of economic alliances, geopolitical tensions, climate change, and technological innovation on global governance. The study adopts a multidisciplinary approach, integrating qualitative and quantitative data analysis to explore the structural transformations shaping international relations. The findings indicate that while economic blocs and emerging technologies foster cooperation and development, challenges such as climate instability and economic inequalities persist. Recommendations include strategic policies to strengthen global cooperation, mitigate climate risks, and leverage technological advancements for sustainable growth.